EFEKTIVITAS PENGGUNAAN MEDIA FLY SWATTER GAME TERHADAP KEMAMPUAN PENGUASAAN KOSAKATA BAHASA MANDARIN - Gantari, Alodya Vania; Churota’ayun, Elisa (Universitas Widya Kartika Surabaya, 2024)
Currently, Mandarin is one of the subjects taught in almost all private schools in Indonesia. Almost all schools have made Mandarin a compulsory subject, including at St. Theresia 1 Catholic Elementary School in Surabaya. However, during the teaching and learning process, both teachers and students encounter many obstacles and challenges. The most common issue in learning Mandarin is recognizing Hanzi characters. Therefore, teachers strive to find appropriate and effective methods to make learning Mandarin easier for students. In this thesis, the author elaborates on the effectiveness of using the Fly Swatter game media for mastering Mandarin vocabulary in class 5B at St. Theresia 1 Catholic Elementary School in Surabaya. This research uses a quantitative approach with a pre-test and post-test design. It concludes that the use of the Fly Swatter game media is effective in improving the learning outcomes of class 5B students at St. Theresia 1 Catholic Elementary School in Surabaya.